2023
DOI: 10.1101/2023.01.05.522945
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global gene expression of human malaria parasite liver stages throughout intrahepatocytic development

Abstract: Plasmodium falciparum(Pf) is causing the greatest malaria burden, yet the liver stages (LS) of this most important parasite species have remained poorly studied. Here, we used a human liver-chimeric mouse model in combination with a novel fluorescentPfNF54 parasite line (PfNF54cspGFP) to isolatePfLS-infected hepatocytes and generate transcriptomes that cover the major LS developmental phases in human hepatocytes. RNA-seq analysis of earlyPfLS trophozoites two days after infection, revealed a central role of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…However, the apparent absence of HSP101 from P. berghei EEFs provides further rationale to characterize PTEX in P. falciparum liver stages. A recent study demonstrated expression of HSP101 at the periphery of P. falciparum EEFs ( 73 ) and a function during the liver stage remains plausible. The FlpL/ FRT system adapted herein provides an ideal approach to address the functional importance of HSP101 in liver stages.…”
Section: Discussionmentioning
confidence: 99%
“…However, the apparent absence of HSP101 from P. berghei EEFs provides further rationale to characterize PTEX in P. falciparum liver stages. A recent study demonstrated expression of HSP101 at the periphery of P. falciparum EEFs ( 73 ) and a function during the liver stage remains plausible. The FlpL/ FRT system adapted herein provides an ideal approach to address the functional importance of HSP101 in liver stages.…”
Section: Discussionmentioning
confidence: 99%